Vaccine conspiracy association with higher COVID-19 vaccination side effects and negative attitude towards booster COVID-19, influenza and monkeypox vaccines: A pilot study in Saudi Universities - Samiyah Alshehri; Malik Sallam (Taylor & Francis Group, 2023)
ABSTRACTConspiracies regarding vaccines are widely prevalent, with negative consequences on health-seeking behaviors. The current study aimed to investigate the possible association between the embrace of vaccine conspiracies and the attitude to booster COVID-19, seasonal influenza, and monkeypox (mpox) vaccinations as well as the perceived side effects following COVID-19 vaccination. The target population involved academic staff and university students in health colleges in the Kingdom of Saudi Arabia. A self-administered questionnaire was distributed in January 2023 to collect data on participants' demographics, self-reported side effects following each dose, willingness to get booster COVID-19, seasonal influenza, and mpox vaccinations, as well as an evaluation of vaccine conspiracies and attitude to mandatory vaccination. Among the 273 participants, the willingness to receive yearly booster COVID-19 vaccination was observed among 26.0% of the participants, while it was 46.9% and 34.1% for seasonal influenza and mpox vaccinations, respectively. Multinomial logistic regression analyses demonstrated a significant correlation between endorsing vaccine conspiracies and higher frequency of self-reported side effects following uptake of the second and third doses of COVID-19 vaccines. Vaccine conspiracies were also correlated with attitude toward booster COVID-19, influenza, mpox, and mandatory vaccination. The findings of this pilot study highlighted the potential adverse impact of the preexisting notions and negative attitudes toward vaccines, which could have contributed to heightened perceived side effects following COVID-19 vaccination. The study also highlighted the ongoing divisions concerning mandatory vaccination policies, emphasizing the need for cautious implementation of this strategy as a last resort for public health benefit.